2022
DOI: 10.1177/20406223221083508
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and health outcomes: An umbrella review of systematic reviews and meta-analyses

Abstract: Purpose: A large number of systemic reviews and meta-analyses have explored the relationship between nonalcoholic fatty liver disease (NAFLD) and multiple health outcomes. The aim of this study is to conduct an umbrella review to assess the strength and evidence for the association between NAFLD and health outcomes. Methods: We systematically identified the present meta-analyses of observational studies reporting an association between NAFLD and health outcomes. For each meta-analysis, we assessed the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Non-alcoholic fatty liver disease (NAFLD) is a multistage disease affecting 30% of the global population, which will supposedly emerge as the most common cause of the end-stage liver disease ( 1 , 2 ). Substantial studies have demonstrated that NAFLD contributes to several disease processes containing hepatic/extrahepatic diseases and an overall increase in mortality ( 3 ). Currently, it is well recognized that the double-hit theory plays a vital role in the pathogenesis of NAFLD ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is a multistage disease affecting 30% of the global population, which will supposedly emerge as the most common cause of the end-stage liver disease ( 1 , 2 ). Substantial studies have demonstrated that NAFLD contributes to several disease processes containing hepatic/extrahepatic diseases and an overall increase in mortality ( 3 ). Currently, it is well recognized that the double-hit theory plays a vital role in the pathogenesis of NAFLD ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD), as a metabolic disease, is the most prevalent hepatic pathology worldwide with a prevalence of approximately 25% [ 1 ]. It ranges from simple steatosis (SS) to advanced stage of nonalcoholic steatohepatitis (NASH), the latter rapid progression toward liver cirrhosis, and hepatocellular carcinoma (HCC) [ 2 , 3 ]. Currently, sensitive biomarkers for the diagnosis of NAFLD are still lacking, and liver biopsies, as an invasive method, are still considered the gold standard for diagnosis and prognosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%